The Caliphate of Imam Ali (Peace Be Upon Him) in the Thought of Abu Ali al- Jubba'i (d. 303 AH-915AD) - Yusuf Saud Al-Sultan , Lect. Dr. Aqeel (Basra studies journal, 2025)
This research examines the perspective of Abu Ali al-Jubba'I —the leader of the Mu'tazila school in Basra and one of its foremost theorists regarding the caliphate of Imam Ali (PBUH) through dialectical methodology, he presented a nuanced view of Ali's caliphate, oscillating between negative and positive. He explicitly criticized his opponents. However, this did not prevent him from opposing certain virtues and textual evidence supporting Ali's divinely ordained succession to the caliphate. This stance likely stems from the doctrinal foundations of the Mu'tazila school and their dialectical nature, as they were among the Islamic sects most reliant on reason and argumentation in all matters.